Anti-Inflammatory State in Arabian Horses Introduced to the Endurance Training - Witkowska-Piłaszewicz, Olga (Animals (Basel), 2019)
SIMPLE SUMMARY: The aim of this study was to investigate whether endurance training changes pro- and anti-inflammatory cytokine profile within a 20-week training season in young inexperienced endurance Arabian horses. It has been suggested that regular endurance training can induce an advanced anti-inflammatory response, but its nature is not completely understood. However, to promote more effective use of endurance exercise training in health promotion and disease prevention, a complete understanding of the nature of its immune regulatory effect is required. The results suggest that endurance training can induce advanced overall anti-inflammatory response as an adaptation to increasing workload. ABSTRACT: Development of an anti-inflammatory state during physical training has been postulated in both human and equine athletes, but it is not completely understood. The aim of this study was to investigate whether endurance training changes pro- and anti-inflammatory cytokine profiles within a 20-week training season in young inexperienced endurance horses. Nine Arabian horses were examined in this prospective 20-week follow-up study. Blood samples were analysed 5 times monthly, at rest and after training sessions. Routine haematological examinations were performed. Cytokine patterns including IL-1β, IL-6, TNF-α, IL-10 mRNA expression using Real Time-PCR, and serum concentrations of IL-1β, IL-2, IL-4, IL-6, IL-17, INFγ, TNF-α, and IL-10 by ELISA test were determined. During endurance training, the most significant decrease in post-exercise cytokine type 1 levels (TNFα and IL-β) occurred within 20 weeks, beginning from the 3rd month of training. IL-6 serum level decreased after the 4th month. The results suggest that endurance training can induce advanced overall anti-inflammatory response as an adaptation to increasing workload.